Battling Protestants : A Conversation with David Hollinger. - Burton, Howard (Toronto : Open Agenda Publishing, 2020)
This book is based on an in-depth filmed conversation between Howard Burton and intellectual historian David Hollinger, UC Berkeley, and examines the unique role that different strands of religion have played in 20th-century American culture. The conversation examines intriguing aspects of the distinction between Ecumenical and Evangelical Protestantism, the often overlooked role of Ecumenical Protestantism in the history of the USA, secularization theory, the development of the two-party system, the role of missionaries, and more. This carefully-edited book includes an introduction, The Excep.
Intro -- A Note on the Text -- Introduction -- The Conversation -- I. Diverging Protestants -- II. Drifting towards Secularism? -- III. Often Overlooked -- IV. The Missionary Position -- V. Demographic Diversification -- VI. William James -- VII. Strident Atheists -- VIII. An Empty Stage -- IX. Future Speculations -- Continuing the Conversation
Description based upon print version of record.
JSTOR
Keywords: Hollinger, David -- Interviews; Protestantism -- United States; Protestantisme -- États-Unis.; Comparative Religion; RELIGION; History; Protestant; Christianity; Protestantism; United States; Interviews